2012
DOI: 10.1016/j.bbr.2011.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine attenuates cognitive impairment after isoflurane anesthesia in old rats

Abstract: Post-operative cognitive dysfunction (POCD) is a clinical phenomenon that has drawn significant attention from the public and scientific community. Age is a risk factor for POCD. However, the contribution of general anesthesia/anesthetics to POCD and the underlying neuropathology are not clear. Here, we showed that 18-month-old male Fisher 344 rats exposed to 1.2% isoflurane, a general anesthetic, for 2 h had significant learning and memory impairments assessed at 2 to 4 weeks after isoflurane exposure. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
82
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 50 publications
(78 reference statements)
6
82
0
Order By: Relevance
“…We and others have shown that neuroinflammation may be the underlying pathology for cognitive impairment after surgery and anesthesia (Cibelli et al 2010;Terrando et al 2011;Cao et al 2012;Lin et al 2012;Vizcaychipi et al 2014;Zhang et al 2014a, b). Our current study showed that surgery induced an increase of inflammatory cytokines, such as IL-1β, and Iba-1, a marker for microglia and leukocytes.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We and others have shown that neuroinflammation may be the underlying pathology for cognitive impairment after surgery and anesthesia (Cibelli et al 2010;Terrando et al 2011;Cao et al 2012;Lin et al 2012;Vizcaychipi et al 2014;Zhang et al 2014a, b). Our current study showed that surgery induced an increase of inflammatory cytokines, such as IL-1β, and Iba-1, a marker for microglia and leukocytes.…”
Section: Discussionmentioning
confidence: 88%
“…Animal studies have shown that isoflurane alone can induce learning and memory dysfunction and mild neuroinflammation Cao et al 2012;Fidalgo et al 2012;Zuo 2012). Neuroinflammation may be the underlying neuropathology for POCD (Cibelli et al 2010;Terrando et al 2011;Cao et al 2012;Lin et al 2012). Thus, it is possible that volatile anesthetics may contribute to the development of POCD.…”
mentioning
confidence: 99%
“…4,5 This finding is consistent with previous studies showing that neuroinflammation is associated with cognitive impairment in humans [7][8][9] and in animals [10][11][12] and that neuroinflammation may contribute to cognitive impairment after isoflurane anesthesia or isoflurane anesthesia plus surgery in adult animals. 10,[12][13][14] it is proposed that perioperative neuroinflammation plays an important role in postoperative cognitive dysfunction and therefore, the resolution of this neuroinflammation after surgery may result in cognitive improvement in adults. 15 Xie's studies extend this detrimental role of neuroinflammation in cognitive impairment to developing brains.…”
Section: "[These] Studies From Xie's Laboratory Suggest An Important mentioning
confidence: 99%
“…However, lidocaine, a local anesthetic with antiinflammatory property, has been shown to reduce isoflurane-induced cognitive impairment and brain expression of inflammatory cytokines in adult animals. 13,14 lidocaine has been commonly used clinically during general anesthesia and may be an alternative for ketorolac to reduce cognitive impairment in the developing brain should its effectiveness be established in the future studies.…”
Section: "[These] Studies From Xie's Laboratory Suggest An Important mentioning
confidence: 99%
“…Therefore, immune modulatory therapy should be considered carefully and is currently still in its infancy in clinical practice. Lidocaine has been commonly used in clinical practice during general anesthesia with anti-inflammatory properties and may be an alternative for the immune modulatory therapies to reduce POCD (34). Furthermore, proper modulation of endogenous anti-inflammatory and proresolving pathways may have the therapeutic potential for preventing/reducing POCD and possibly other perioperative and neurodegenerative conditions (18,35,36).…”
mentioning
confidence: 99%